A constitutive model for elastoplastic-damage coupling effect of unidirectional fiber-reinforced polymer matrix composites. (March 2020) - Chen, Yanfei; Zhao, Yunong; Ai, Shigang; He, Chunwang; Tao, Yong; Yang, Yazheng; Fang, Daining
Abstract: In this paper, an elastoplastic-damage coupling constitutive model for unidirectional fiber-reinforced polymer matrix composites (UD FRPs) is presented, which both considers the plastic-hardening and damage-softening processes. Tension-compression asymmetry and shear strength increase due to transverse compression are observed under off-axis tensile/compressive tests of UD E-glass/YPH-200. Therefore, a four-parameter plastic yield criterion considering these two effects is proposed. Applying this model to predict the off-axis tensile/compressive responses of present tests provides good agreement with experimental curves. In addition, we give a novel definition of shear damage variable based on Puck failure theory and discuss it in detail. Further, we develop a four-parameter matrix failure criterion for UD FRPs and exactly predict the off-axis failure strength.